NATALIA BLOCH, Encounters across Difference. Tourism and Overcoming Subalternity in India - Malewska-Szałygin, Anna (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2023)
Recenzja książki Natalii Bloch, Encounters across Difference. Tourism and Overcoming Subalternity in India.